Effects of dietary beta-agonist treatment, Vitamin D3 supplementation and electrical stimulation of carcasses on meat quality of feedlot steers - Webb, E.C. (Edward Cottington) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.